1923 Cal. Stat. 698-99 - (:unkn) unknown (My University, 1923)
Ch. 339, § 8: Allowed the Sheriff or the county and the board of police commissioners, chief of police, town martial, or other police department to require proof of good moral character for the issuance of a license for a concealed pistol, revolver, or other firearm for a period of one year.
Keywords: PEACE OFFICERS; LICENSE - CARRY - CONCEALED